2009
DOI: 10.1364/ao.48.001610
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared active polarimetric and multispectral laboratory demonstrator for target detection

Abstract: We report on the design and exploitation of a real-field laboratory demonstrator combining active polarimetric and multispectral functions. Its building blocks, including a multiwavelength pulsed optical parametric oscillator at the emission side and a hyperspectral imager with polarimetric capability at the reception side, are described. The results obtained with this demonstrator are illustrated on some examples and discussed. In particular it is found that good detection performances rely on joint use of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 27 publications
(32 reference statements)
1
21
0
Order By: Relevance
“…In this section we will show how this system enables a good OSC estimation in real conditions. In particular, we will carry out experiments in situations where systems based on sequential acquisition [3,14,27] show weakness and imprecision. The system designed in this paper can also be operated in a sequential acquisition mode to show the benefit of simultaneous acquisition: one just has to consider the parallel image X in an acquisition and the orthogonal image Y in the subsequent acquisition.…”
Section: Validation Of Concept On Some Real Situationsmentioning
confidence: 99%
“…In this section we will show how this system enables a good OSC estimation in real conditions. In particular, we will carry out experiments in situations where systems based on sequential acquisition [3,14,27] show weakness and imprecision. The system designed in this paper can also be operated in a sequential acquisition mode to show the benefit of simultaneous acquisition: one just has to consider the parallel image X in an acquisition and the orthogonal image Y in the subsequent acquisition.…”
Section: Validation Of Concept On Some Real Situationsmentioning
confidence: 99%
“…The polarizers are oriented at 0° (), 45° (), 90° () from the horizontal state of polarization of the source. First, we identify the polarimetric behavior of the scene with an Orthogonal States Contrast (OSC) imaging approach which is well adapted to target detection application 1,4,5,13 but requires two acquisitions. For this reason, we have slightly modified the illumination stage of the demonstrator to perform a full field OSC imaging technique.…”
Section: Imaging Results On Artifical Scenariosmentioning
confidence: 99%
“…At the same time, it reduces drastically the ocular hazard when operating with powerful illumination source, as the first layers of the eye absorb strongly infrared light thus preserving the retina. In the literature, most of the NIR active polarimetric imagers use the OSC technique [1][2][3][4][5] since it is able to discriminate non-depolarizing man-made objects from a depolarizing natural environment with only two acquisitions using crossed polarizers at the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thales and CNRS in France in collaboration with Norsk Elektro Optikk (Norway) report on the design and exploitation of a real-field laboratory demonstrator [4]. It was found that good detection performances rely on the joint use of intensity and polarimetric images, with these images exhibiting complementary signatures in most cases.…”
Section: Laboratory Investigations Of Active Spectral Imaging-hard Tamentioning
confidence: 99%